THE USE OF JOHNNY COMMUNICATION CENTER YOUTUBE VLOG IN LEARNING VOCABULARY FOR YOUNG NCTZENS - Qonita, Asmaul; Hateem, Zaitun (Linguistik : Jurnal Bahasa dan Sastra, 2023)
When learning English, students must balance the four language skills to be competent in spoken and written English. And vocabulary is required to support those four skills. It is easier for students to acquire each skill if they have a minimal bank of words. This study was conducted to determine whether or not the effectiveness of using Vlog content in vocabulary learning for young NCTZen aged 12-16 years. This research uses a quantitative descriptive method. Data collection was carried out by distributing questionnaire in the form of Google Form to 100 young NCTZen. After conducting the study, the findings revealed that 56.9% of participants agreed and thought JCC content was a useful resource for learning vocabulary to young NCTZen. 6.85% of respondents gave neutral responses. While 36.7% of respondents responded disagree. From those results, it may be inferred that the majority of respondents felt that JCC Content was effective